BiOI / WO3 nanorod array composite photoelectrode and preparation method and application thereof
By depositing BiOI on the WO3 nanorod array list surface, the BiOI/WO3 nanorod array composite photoelectrode was prepared, which solved the problems of small surface area and poor catalytic performance of the existing photoelectrode, and achieved the effect of efficient degradation of antibiotic wastewater.
Patent Information
- Application Number
- CN202411751172.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing composite photoelectrodes have problems such as small surface area, few active sites and poor photocatalytic performance, making it difficult to efficiently degrade antibiotic wastewater.
The solvothermal method was used to deposit BiOI on the WO3 nanorod array list surface to prepare the BiOI/WO3 nanorod array composite photoelectrode, forming a three-dimensional structure with a large specific surface area, many active sites and strong light absorption and utilization ability.
The photoelectrocatalytic performance is improved, and the photogenerated carriers can be efficiently separated under light and electric fields, significantly improving the degradation efficiency of antibiotics.
Smart Images

Figure CN119409290A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new environmental materials and their applications, and in particular relates to a BiOI / WO3 nanorod array composite photoelectrode and a preparation method and application thereof. Background Art
[0002] With the widespread use of various antibiotic drugs, antibiotics and their metabolites have entered the environmental system in large quantities, posing a potential threat to the ecological environment and human health. Antibiotics are non-biodegradable organic matter. Traditional wastewater treatment methods have poor treatment effects on antibiotic wastewater. Therefore, there is an urgent need to develop new technologies that can effectively treat antibiotic wastewater. Advanced oxidation method is one of the most effective methods for treating antibiotic wastewater. Photocatalysis and photoelectrocatalysis (PEC) as a new advanced oxidation method have good effects on antibiotic degradation and have attracted widespread attention from researchers. Photoelectrocatalytic technology has the following advantages: (1) The catalyst on the photoelectrode is fixed, does not need to be separated, and is easy to reuse, which solves the problem of separation and recovery of nanoparticle photocatalysts; (2) The bias voltage applied to the photoelectrode can drive the photogenerated electrons to transfer to the external circuit, thereby effectively improving the separation efficiency of photogenerated electrons and holes. Therefore, the photoelectrocatalytic degradation of antibiotics in wastewater is more efficient. The research and development of photoelectrodes with high catalytic activity is a key link in photocatalytic technology.
[0003] Compared with ordinary WO3 thin films, WO3 nanorod arrays have a three-dimensional structure and are an ideal basis for constructing composite photoelectrodes. WO3 has a narrow band gap and is a visible light-responsive n-type photocatalyst that has been widely studied in the photocatalytic removal of organic pollutants in water. However, single WO3 still has the problem of fast photoelectron-hole recombination rate, so the photocatalytic activity is not high. Constructing a heterojunction photoelectrode combined with other photocatalysts is one of the most effective ways to improve the photocatalytic activity of WO3. However, existing composite photoelectrodes still have problems such as small surface area, few active sites, and poor photoelectrocatalytic performance.
[0004] Therefore, there is an urgent need to provide a BiOI / WO3 nanorod array composite photoelectrode with a large specific surface area, multiple active sites, strong light absorption and utilization ability, and the ability to efficiently degrade antibiotics, and a preparation method thereof. Summary of the invention
[0005] In view of the above technical problems, the present invention proposes a BiOI / WO3 nanorod array composite photoelectrode and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a BiOI / WO3 nanorod array composite photoelectrode comprises the following steps:
[0009] dissolving a bismuth source and an iodine source in an organic solvent to form a mixed solution;
[0010] The FTO glass with the WO3 nanorod array film on the surface is immersed in the mixed solution, heated, and cooled to obtain the BiOI / WO3 nanorod array composite photoelectrode.
[0011] Preferably, the bismuth source is Bi(NO3)3·5H2O; and the iodine source is KI.
[0012] Beneficial effect: In the present invention, the bismuth source is limited to Bi(NO3)3·5H2O because it has good solubility and can react better with the iodine source in a limited solvent.
[0013] Furthermore, the molar ratio of the bismuth source to the iodine source is 1:1.
[0014] Preferably, the organic solvent is ethylene glycol methyl ether, ethylene glycol or a mixture of ethanol and ethylene glycol (volume ratio 1:1).
[0015] Preferably, the conditions during the heating process are: reacting at 150-170° C. for 10-14 hours.
[0016] Preferably, the preparation process of the FTO glass with the WO3 nanorod array film on the surface is:
[0017] WO3 nanorod array thin films were prepared on the surface of fluorine-doped tin dioxide (FTO) conductive glass by hydrothermal method and annealed at 500℃ for 3h.
[0018] The second technical solution of the present invention:
[0019] A BiOI / WO3 nanorod array composite photoelectrode is prepared by the above preparation method.
[0020] Preferably, the BiOI / WO3 nanorod array composite photoelectric pole is an irregular three-dimensional porous structure.
[0021] The third technical solution of the present invention:
[0022] The application of the BiOI / WO3 nanorod array composite photoelectrode in the field of photoelectrocatalytic purification of antibiotic wastewater.
[0023] Preferably, the antibiotic is CIP (ciprofloxacin).
[0024] The fourth technical solution of the present invention:
[0025] A method for photoelectrocatalytic degradation of CIP, under the conditions of external illumination and applied bias voltage, utilizes the two-electrode or three-electrode system of the BiOI / WO3 nanorod array composite photoelectrode to degrade CIP.
[0026] Preferably, the three-electrode system is:
[0027] 0.1 M Na2SO4 was used as the electrolyte solution, the BiOI / WO3 nanorod array photoelectrode was used as the working electrode, Ag / AgCl (3.0 M KCl) was used as the reference electrode, and the platinum sheet electrode was used as the counter electrode.
[0028] Preferably, the illumination condition is: using a 500W xenon lamp as the light source and filtering out light with a wavelength less than 400nm; and / or
[0029] The bias voltage is 1.2-1.6V.
[0030] Furthermore, the bias voltage is 1.2V.
[0031] Compared with the prior art, the present invention has the following advantages and technical effects:
[0032] (1) In the BiOI / WO3 nanorod array composite photoelectrode prepared by the present invention, BiOI ultrathin nanosheets are uniformly attached to the surface of the WO3 composite nanorod array to form a three-dimensional structure, the active sites are fully exposed, the specific surface area is large, and the catalytic performance is effectively improved.
[0033] (2) The BiOI / WO3 nanorod array composite photoelectrode prepared by the present invention can effectively separate photogenerated carriers under light and electric field, thereby fundamentally improving the performance of catalytic degradation and efficiently degrading organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0035] Figure 1 The XRD pattern of the BiOI / WO3 nanorod array photoelectrode prepared in Example 1-5;
[0036] Figure 2 SEM images of WO3 nanorod arrays (a, b) and BIW-1.2 (c, d) prepared in Example 1;
[0037] Figure 3 TEM images (ae) and EDX elemental analysis diagrams (fk) of BIW-1.2 nanorods prepared in Example 1;
[0038] Figure 4 This is the X-ray photoelectron spectrum of the BIW-1.2 nanorods prepared in Example 1;
[0039] Figure 5 (a) Linear sweep voltammetry and (b) transient photocurrent response curves of the BiOI / WO3 nanorod array photoelectrode prepared in Examples 1-5;
[0040] Figure 6 The UV diffuse reflectance spectrum (a), Tauc curve (b), Mott-Schottky curve (c) and energy band distribution diagram (d) of the BiOI / WO3 nanorod array photoelectrode prepared in Examples 1-5;
[0041] Figure 7 Comparison of the CIP degradation performance of the BiOI / WO3 nanorod array photoelectrode prepared in Example 1 as different catalysts (a) and different catalytic methods (b); the effect of bias voltage on degradation efficiency (c) and cyclic degradation test (d);
[0042] Figure 8 DMPO-·O2 - EPR spectra of adduct (a), DMPO-·OH adduct (b), and PEC degradation images of CIP by different free radical scavengers (c);
[0043] Fig. 9 The charge separation of the BIW-1.2 nanorod array prepared in Example 1 and the mechanism diagram of PEC degradation of CIP;
[0044] Fig.10 This is a comparison chart of the BIW-1.2 nanorod array prepared in Example 1 of the present invention and BiOI(7h) / WO3 in Comparative Example 1 as photoelectrodes for degrading CIP. DETAILED DESCRIPTION
[0045] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0046] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0047] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0048] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0049] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0050] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0051] The raw materials used in the present invention are all purchased from the market.
[0052] The technical solution of the present invention is further illustrated by the following embodiments.
[0053] Example 1
[0054] BiOI was deposited on the surface of WO3 nanorod array by solvothermal method to prepare BiOI / WO3 nanorod array photoelectrode. The specific process is as follows:
[0055] First, a WO3 nanorod array film was prepared on the surface of fluorine-doped tin dioxide (FTO) conductive glass by a hydrothermal method and annealed at 500°C for 3h. The specific steps of the hydrothermal method are as follows:
[0056] 0.8g of ammonium metatungstate was added to 75mL of deionized water and stirred until completely dissolved. Then, 2.5mL of concentrated HCl was added and stirred for 30 minutes. 2mL of H2O2 was added and stirred vigorously for 1 hour. The solution turned into a transparent state. The fluorine-doped tin dioxide (FTO) conductive glass was placed in a 100mL hydrothermal kettle, and the prepared solution was slowly poured in. After sealing, the reaction was heated at 160°C for 4 hours. After the reaction was completed, the hydrothermal kettle was naturally cooled to room temperature, the FTO glass was taken out, and the surface was rinsed with deionized water and dried in an oven at 80°C for 30 minutes. The dried FTO was placed in a box-type resistance furnace and calcined at 500°C for 3 hours to obtain FTO glass with a WO3 nanorod array film on the surface.
[0057] Secondly, synthesize BiOI / WO3 nanorod arrays: first dissolve 1.2mmol Bi(NO3)3·5H2O and 1.2mmol KI in 80mL ethylene glycol methyl ether; then slowly pour the mixed solution into the lining of a 100mL stainless steel hydrothermal autoclave, which contains two pieces of FTO glass (WO3 nanorod array film prepared on the surface), and react at 160℃ for 12h. Then naturally cool to room temperature, take out the prepared photoelectrode product, rinse it with distilled water, put it in a forced air drying oven and dry it at 75℃, and prepare the BiOI / WO3 nanorod array labeled as BIW-1.2.
[0058] Embodiment 2-5
[0059] On the basis of Example 1, different BiOI / WO3 nanorod arrays were prepared by using different addition amounts of Bi(NO3)3·5H2O and KI. The remaining steps and parameters were the same as those in Example 1, as follows:
[0060] Bi(NO3)3·5H2O 0.4mmol, KI 0.4mmol; marked as BIW-0.4 (Example 2);
[0061] Bi(NO3)3·5H2O 0.8mmol, KI 0.8mmol; marked as BIW-0.8 (Example 3);
[0062] Bi(NO3)3·5H2O 1.6mmol, KI 1.6mmol; marked as BIW-1.6 (Example 4);
[0063] Bi(NO3)3·5H2O 2mmol, KI 2mmol, marked as BIW-2 (Example 5).
[0064] Comparative Example 1
[0065] Refer to the preparation process of BiOI(7h) / WO3 prepared in the literature "Bidirectionally Regulated Ultraviolet and Visible Dual-Band Photoresponse Characteristics of Self-Powered BiOI / WO3 Photodetectors".
[0066] Effect verification
[0067] (I) Measurement of photoelectric properties of photoelectrodes
[0068] The electrochemical workstation (CHI 660E, Shanghai Chenhua Instrument) used a three-electrode system to test the electrochemical and photoelectric properties in a 0.1M Na2SO4 electrolyte solution, with BiOI / WO3 nanorod array photoelectrode as the working electrode, Ag / AgCl (3.0M KCl) as the reference electrode, and platinum electrode as the counter electrode. A 500W xenon lamp was used as the light source, and an electric shutter was added at the light source outlet to measure the open circuit potential, transient photocurrent, and linear sweep voltammetry test.
[0069] (II) BiOI / WO3 nanorod array photoelectrode PEC degradation of CIP
[0070] The experiment of PEC degradation of CIP was carried out in a small photoelectric reactor with a quartz glass window. A 500W xenon lamp was used for illumination. A UV cutoff filter (UVcut 400) was installed at the light source outlet to filter out light with a wavelength less than 400nm. The above three-electrode system was used, with BiOI / WO3 nanorod array as the working electrode (effective area of 2cm 2 ). During the experiment, 15 mL of CIP solution with an initial concentration of 20 mg / L was loaded into the photoelectric reactor. The absorbance of CIP was measured at a wavelength of 272 nm using an ultraviolet spectrophotometer, and the concentration of CIP was calculated based on the absorbance-concentration standard curve. At the beginning of the experiment, the reactor containing the CIP solution was placed in the dark for 30 minutes to allow the catalyst and CIP to reach adsorption equilibrium. The initial concentration of CIP (C0) was measured before illumination. After the light reaction started, the solution was extracted every 0.5 h to measure the CIP (C t ) concentration. Using η=(C0-C t ) / C0 to calculate the degradation efficiency. Each time the CIP concentration is measured, the light source is shielded and the photocatalytic reaction is suspended. When the photoelectrode stability cycle test is performed, the photoelectrode remains unchanged. After each degradation reaction process is completed, a new CIP solution is replaced for degradation reaction.
[0071] The present invention adopts a solvothermal method to prepare a series of BiOI / WO3 nanorod array composite photoelectrodes. The BiOI nanosheets grown on the surface of the WO3 nanorods have strong binding force, and the photoelectrode is a three-dimensional structure, with the characteristics of large specific surface area, multiple active sites, and strong light absorption and utilization ability. The morphology, composition, photoelectric performance and energy band structure of this series of photoelectrodes are systematically characterized and studied; and the catalytic degradation activity of the photoelectrode is evaluated by using the method of photocatalytic degradation of ciprofloxacin (CIP); and the photoelectrochemical properties, energy band structure and free radical types in the degradation reaction of the photoelectrode are further analyzed, and its photocatalytic degradation mechanism is analyzed.
[0072] Figure 1XRD diagram of BiOI / WO3 nanorod array (NRAs) photoelectrode prepared in Example 1-5; from the diffraction peak of WO3 nanorod array, it can be concluded that it belongs to monoclinic crystal (JCPDS card number 43-1035); BiOI belongs to pure tetragonal crystal (JCPDS card number 10-0445), and the characteristic diffraction peaks at 29.6°, 31.7°, 45.4° and 55.2° correspond to (102), (110), (200) and (212) crystal planes, respectively; for BIW composite material, with the increase of BiOI, the diffraction peak intensity of BiOI gradually increases, while the diffraction peak intensity of WO3 gradually decreases, indicating that WO3 phase and BiOI phase coexist in the material of composite photoelectrode; the photoelectrode has the diffraction peak of SnO2, which is the signal of SnO2 in FTO glass conductive layer.
[0073] Figure 2 SEM images of WO3 nanorod arrays (a, b) and BIW-1.2 (b, d) prepared in Example 1; Figure 2 As shown in a and b, the WO3 nanorod arrays are evenly distributed on the FTO substrate, and there are many pores between the nanorods; Figure 2 Figures c and d are SEM images of BIW-1.2 photoelectrodes, from which we can see that BiOI nanosheets intertwined with each other grow on WO3 nanorods to form an irregular three-dimensional porous structure. This three-dimensional structure has a huge specific surface area, can provide more catalytic active sites, and can also improve the absorption and utilization efficiency of photons, thereby improving the photocatalytic performance.
[0074] Figure 3 TEM images (ae) and EDX elemental analysis diagrams (fk) of BIW-1.2 nanorods prepared in Example 1; Figure 3 As shown in a, after the nanorods removed from the BIW-1.2 film were dispersed by ultrasound, the BiOI nanosheets were also tightly bound to the surface of the WO3 nanorods, indicating that there was a strong crystallization force between the two; the BiOI nanosheets were tightly bound to the WO3 nanorods and had a staggered interface ( Figure 3 In b and e), the contact interface is conducive to photocarrier transfer; Figure 3 As can be seen in Figure e, the (002) crystal plane lattice fringes of WO3 are very clear, indicating good crystallinity, with a lattice spacing of 0.382nm; the lattice fringes spacing is 0.276nm, corresponding to the (110) crystal plane of BiOI; Figure 3 hk is the element mapping of Bi, O, I and W in BIW-1.2; it is not difficult to find from the element distribution diagram that the distribution of each element is consistent with the shape of the composite material, which further proves that BiOI is uniformly distributed on the surface of WO3 nanorods, which is consistent with the SEM results.
[0075] Figure 4is the X-ray photoelectron spectrum of the BIW-1.2 nanorods prepared in Example 1; Figure 4 As shown in (a), W, Bi, I and O were observed in the scanning spectrum, indicating that BiOI and WO3 were successfully assembled together; Figure 4 In (b), two obvious peaks appear at 159.34 eV and 164.64 eV, corresponding to Bi 4f 7 / 2 and Bi 4f 5 / 2 Atomic orbitals of Figure 4 There are two peaks centered at 619.23 eV and 630.71 eV in c, which are respectively related to I 3d 5 / 2 and I 3d 3 / 2 orbital related; in addition, Figure 4 The two peaks in the middle d at binding energies of 35.75 eV and 37.87 eV belong to W 4f 7 / 2 and W 4f 5 / 2 ; O1s spectrum ( Figure 4 There are three peaks in (e), the two peaks with binding energies of 530.15 eV and 531.99 eV are attributed to the lattice oxygen of Bi-O and WO bonds, respectively, while the peak at 530.82 eV belongs to the hydroxyl group.
[0076] Figure 5 The (a) linear sweep voltammetry and (b) transient photocurrent response curves of the BiOI / WO3 nanorod array photoelectrode prepared in Examples 1-5 are shown; Figure 5 As shown in a, the linear sweep voltammetry (LSV) method was used to study the effect of the bias voltage on the photocurrent. In the dark state (shutter closed), no current was generated on the photoelectrode, but when the bias voltage was higher than about 1.5V, current began to appear on all photoelectrodes, which was the current generated by the breakdown of the photocatalyst film. When light was irradiated on the photoelectrode (shutter open), the photocurrent appeared instantly. As the bias voltage increased, the photocurrent density also increased rapidly. When the bias voltage reached about 1.2V, the increase in photocurrent became smaller. This is because the photogenerated electrons flowed to the counter electrode under the drive of the bias voltage, and the bias voltage was the driving force. When the bias voltage increased to 1.2V, most of the free photogenerated electrons were driven by the bias to migrate to the external circuit. Since there were fewer remaining photoelectrons, the bias voltage continued to increase, so the increase in current was correspondingly smaller. The photocurrent density of the BIW-1.2 nanorod array photoelectrode was higher than that of the WO3 photoelectrode, indicating that the photoelectrode can generate more photogenerated electrons and holes, that is, its PEC performance is better.
[0077] In order to further study the photoelectric performance of the photoelectrode, transient photocurrent tests were carried out ( Figure 5In b), the bias voltage applied to the electrode is 1.2V. When the shutter is closed, the current in the circuit is zero; when the shutter in front of the xenon lamp is opened, a current transient appears on the electrode, the current is large at first, and then basically remains at a certain value. The photocurrent of the WO3 nanorod array is the lowest, which is maintained at -0.05mA / cm 2 As the amount of BiOI on WO3 increases, the photocurrent on the photoelectrode gradually increases. The photocurrent of the BIW-1.2 nanorod array is the largest, maintaining at about -0.1 mA / cm 2 , while the photocurrent of BIW-1.6 nanorod array decreased. This result shows that the current is generated by the photocatalyst on the photoexcited photoelectrode, and the photocurrent density is large when the photoelectron concentration is high. The photocurrent density of BIW-1.2 nanorod array is the highest because WO3 and BiOI form a pn heterojunction and have a three-dimensional structure, which greatly improves the separation efficiency of photogenerated electrons.
[0078] Figure 6 The UV diffuse reflectance spectrum (a), Tauc curve (b), Mott-Schottky curve (c) and energy band distribution diagram (d) of the BiOI / WO3 nanorod array photoelectrode prepared in Example 1 are shown in FIG. Figure 6 In (a), the light absorption edge of the BiOI / WO3 composite nanorod array is about 540nm, which is about 90nm higher than the 450nm of the single WO3 photoelectrode, indicating that the BiOI / WO3 composite nanorod array can absorb and utilize a wider range of visible light. Figure 6 (b) shows that the band gap energy (Eg) of WO3 is 2.70eV, and the Eg of BiOI is 1.93eV; Figure 6 In (c), it can be concluded that the slope of the Mott-Schottky curve of BiOI is negative, indicating that BiOI is a p-type semiconductor with a valence band (VB) potential of 2.26 V (vs. Ag / AgCl); WO3 is an n-type photocatalyst, so it can be considered that its flat band potential (E fb ) and its conduction band potential (E CB ) is approximately equal, and the band structure of WO3 has been studied. According to the formula: E(NHE)=E(Ag / AgCl)+0.212V and E VB =E CB +Eg, the E of BiOI can be calculated VB The value of is 2.47V (vs. NHE), E CB 0.54V; Figure 6 (d) is the band structure distribution diagram of BiOI and WO3.
[0079] Figure 7The following are the performance comparison diagrams of a series of BiOI / WO3 nanorod array photoelectrodes prepared in Examples 1-5 as different catalysts (a) and different catalytic methods (b) for degradation of CIP; the effect of bias voltage on degradation efficiency (c) and cyclic degradation test (d); Figure 7 As can be seen in (a), the efficiency of photocatalytic degradation of CIP by WO3 nanorod array alone is low. With the increase of BiOI on WO3, the efficiency of CIP degradation increases first and then decreases. Among them, the degradation efficiency of BIW-1.2 nanorod array is the highest. This is because the ratio of BiOI and WO3 in BIW-1.2 nanorod array is the best, with more active sites and photogenerated charges, so it has the best catalytic activity. Figure 6 The results of the optoelectronic performance analysis are consistent with the analysis.
[0080] The effects of different catalytic systems on the degradation of CIP are as follows Figure 7 In (b), the applied bias voltage is 1.2V. In the dark state, the BIW-1.2 nanorod array performs electrocatalytic (EC) degradation of CIP. After 3 hours, CIP is basically not degraded, which indicates that the photoelectrode does not electrocatalytically degrade CIP at this voltage. When no catalyst is added to the CIP solution and no bias is applied to the electrode, only 5.6% is degraded in 3 hours, indicating that CIP is relatively stable and not easily photolyzed under visible light. When the BIW-1.2 nanorod array is not biased and only irradiated with a xenon light source, the system degrades CIP by 41.2%, which is the effect of photocatalytic (PC) degradation. When the photoelectrode is under light irradiation and a bias of 1.2V is applied, the efficiency of BIW-1.2 nanorod array in degrading CIP is significantly improved, reaching 97.1% within 3 hours, which is 2.1 times that of photocatalytic degradation alone. The reason for this experimental result is that the bias voltage on the photoelectrode can drive a large number of photogenerated electrons into the external circuit, thereby greatly reducing the recombination probability of photogenerated electrons and holes, and fundamentally improving the catalytic performance of the photocatalyst.
[0081] from Figure 7It can be seen in (c) that as the bias voltage applied to the BIW-1.2 nanorod array photoelectrode increases, the degradation efficiency of CIP increases rapidly at first, then remains stable, and finally decreases. When the applied bias voltage increases from 0.4V to 1.2V, the degradation efficiency of CIP increases greatly. When the bias voltage is 1.2V, the degradation efficiency of CIP reaches 97.1%. As the bias voltage continues to increase, the increase in the degradation efficiency of CIP becomes very slow. When the bias voltage reaches 2.0V, the degradation efficiency of CIP decreases instead. The reason for this is that the bias voltage can effectively transfer photogenerated electrons, thereby reducing the amount of recombination of photogenerated electrons and holes. When the bias voltage on the photoelectrode increases to 1.2V, the free photogenerated electrons have been basically driven into the external circuit by the bias voltage. Therefore, if the bias voltage continues to increase, the degradation efficiency will not increase significantly. When the bias voltage increases to 2.0V, due to the high potential, O2 may be generated on the electrode surface, resulting in a decrease in the amount of free radicals generated on the electrode, and thus the CIP degradation efficiency will decrease. Comprehensive analysis shows that 1.2V is a more appropriate bias voltage.
[0082] from Figure 7 As shown in (d), the photostability of BIW-1.2 nanorod array photoelectrodes was studied by repeatedly performing CIP degradation experiments. After four cycles of use, the degradation efficiency of CIP by BIW-1.2 nanorod arrays decreased slightly, indicating that it has good stability and can be reused.
[0083] Figure 8 DMPO-·O2 - EPR spectra of adduct (a), DMPO-·OH adduct (b), and PEC degradation images of CIP by different free radical scavengers (c); Figure 8 As can be seen, DMPO (5,5-dimethyl-1-pyrroline-N-oxide) was used as a scavenger, and free radical electron paramagnetic resonance (EPR) test was carried out under xenon lamp irradiation to analyze ·OH and ·O2 - The existence of Figure 8 As shown in (a) and (b), in the absence of light, no peak appears; when light is irradiated, Figure 8 As shown in (a), the four DMPO-·OH characteristic peaks that appear indicate the generation of ·OH. The longer the irradiation time, the greater the intensity of the characteristic peaks, indicating that ·OH is generated by light irradiating the photoelectrode. Figure 8 As shown in (b), when there is light irradiation, six peaks appear, of which two small peaks overlap, which is DMPO-·O2 - The characteristic peaks of BIW-1.2 nanorod arrays indicate that ·O2 -The active species in the photocatalytic process of BIW-1.2 nanorod arrays were studied by free radical capture experiments, such as Figure 8 As shown in (c), when the scavenger tert-butyl alcohol (TBA) or triethanolamine (TEOA) is present in the CIP solution, the CIP degradation efficiency is reduced by more than half compared with that without adding the scavenger, which indicates that ·OH and holes are the main active species in the photoelectrocatalytic degradation of CIP by BIW-1.2 nanorod arrays. When benzoquinone (BQ) is added to the CIP solution, the degradation efficiency drops from 97.1% to 58.5%, indicating that ·O2 - The BIW-1.2 nanorod array also plays an important role in the photoelectrocatalytic degradation of CIP. The results of the capture agent experiment are consistent with the EPR experiment results.
[0084] Fig. 9 The diagram is a mechanism diagram of charge separation and PEC degradation of CIP for the BIW-1.2 nanorod array prepared in Example 1; under visible light irradiation, both WO3 nanorods and BiOI nanosheets can generate photogenerated electrons and holes. BiOI is a p-type semiconductor, and its Fermi level is close to VB; WO3 is an n-type semiconductor, and its Fermi level is near CB. After the BiOI / WO3 pn heterojunction is formed, the energy level of BiOI rises, while the energy level of WO3 decreases until the Fermi levels of BiOI and WO3 reach equilibrium. In the equilibrium state, an internal electric field is formed, the p-type BiOI region is negatively charged, and the n-type WO3 region is positively charged. Therefore, the photoelectrons in the CB of BiOI will be transferred to the CB of WO3 under the action of the electric field, and flow to the counter electrode driven by the bias voltage, and interact with the O 2 Reaction to form O2 - , achieving rapid electron transfer and separation. At the same time, the holes in the VB of WO3 will also migrate to the VB of BiOI and react with H2O to generate ·OH. Therefore, the photogenerated electrons and holes of the BIW-1.2 nanorod array are effectively separated, and ·OH, ·O2 - As well as some unreacted holes in the VB of BiOI, they all participated in the photoelectrocatalytic degradation of CIP. In addition, the BIW-1.2 nanorod array can provide more active sites due to its three-dimensional spatial structure, thereby enhancing its PEC degradation activity for CIP. Overall, the embedded electric field of the pn heterojunction formed in the BIW-1.2 nanorod array promotes the separation of photogenerated electrons and holes, and the bias voltage further improves the charge separation efficiency, enhancing the PEC degradation activity of the BIW-1.2 nanorod array.
[0085] Fig.10This is a comparison chart of the degradation of CIP by the BIW-1.2 nanorod array prepared in Example 1 of the present invention and the BiOI(7h) / WO3 in Comparative Example 1. It can be seen from the figure that when the photoelectrode is under light irradiation and a bias of 1.2V is applied, the efficiency of CIP degradation by the BIW-1.2 nanorod array reaches 97.1% after 3 hours, and the efficiency of CIP degradation by BiOI(7h) / WO3 is 71.3%.
[0086] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a BiOI / WO3 nanorod array composite photoelectrode, characterized in that: The following steps are involved: dissolving a bismuth source and an iodine source in an organic solvent to form a mixed solution; The FTO glass with the WO3 nanorod array film on the surface is immersed in the mixed solution, heated, and cooled to obtain the BiOI / WO3 nanorod array composite photoelectrode.
2. The method for preparing a BiOI / WO3 nanorod array composite photoelectrode according to claim 1, characterized in that: The bismuth source is Bi(NO3)3·5H2O; and the iodine source is KI.
3. The method for preparing a BiOI / WO3 nanorod array composite photoelectrode according to claim 2, characterized in that: The molar ratio of the bismuth source to the iodine source is 1:
1.
4. The method for preparing a BiOI / WO3 nanorod array composite photoelectrode according to claim 1, characterized in that: The organic solvent is ethylene glycol methyl ether, ethylene glycol, or a mixture of ethanol and ethylene glycol.
5. The method for preparing a BiOI / WO3 nanorod array composite photoelectrode according to claim 1, characterized in that: The conditions in the heating process are: reacting at 150-170° C. for 10-14 hours.
6. A BiOI / WO3 nanorod array composite photoelectrode, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 5.
7. The BiOI / WO3 nanorod array composite photoelectrode according to claim 6, characterized in that: The BiOI / WO3 nanorod array composite photoelectric structure is an extremely irregular three-dimensional porous structure.
8. Use of the BiOI / WO3 nanorod array composite photoelectrode as claimed in claim 6 in the field of photoelectrocatalytic purification of antibiotic wastewater.
9. A method for photoelectrocatalytic degradation of CIP, characterized in that: Under the conditions of external illumination and applied bias voltage, a two-electrode or three-electrode system including the BiOI / WO3 nanorod array composite photoelectrode is used to degrade CIP.
10. The method for photoelectrocatalytic degradation of CIP according to claim 9, characterized in that: The illumination conditions are: using a 500W xenon lamp as the light source and filtering out light with a wavelength less than 400nm; and / or The bias voltage is 1.2-1.6V.
Citation Information
Patent Citations
Preparation method and application research of WO3 nanosheet array film
CN105384358A
Method for preparing BiOI / WO3 composite heterojunction photocatalyst
CN105688953A
Preparation method, product and application of BiOI / WO3 heterojunction efficient photoelectrocatalysis electrodes
CN110368962A
Fe / WO3 / BiOBr monatomic catalyst, preparation method thereof and application of Fe / WO3 / BiOBr monatomic catalyst in visible light catalytic degradation of ciprofloxacin
CN116078410A